The effect of smoking degree on the incidents of cataracts. - Rahma, Nyimas Salsabila; Ayu Rezkitha, Yudith Annisa; Prameswari, Kaniraras Lintang; Prahasanti, Kartika (Gaceta Médica de Caracas, 2021)
ntroduction: A cataract is a condition of the eye lens experiencing turbidity. It is the highest cause of blindness in the world. Smoking is one of the risk factors for cataracts. According to the Brinkman index, the degree of smoking is a multiplication between smoking time and the number of cigarettes consumed in a day. This study aims to analyze the influence of smoking degree on cataracts.